ANALYSIS OF ANTIDIABETIC DRUGS ASSORTMENT REPRESENTED ON THE PHARMACEUTICAL MARKET OF SAINT PETERSBURG - Yu. V. Miroshnichenko; Yu. A. Vasyagina; M. P. Scherba (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2015)
Optimization of pharmaceutical support of patients with diabetes mellitus who have to use expensive drugs for the life term is particularly marked among the important problems for a healthcare of international society countries including the Russian Federation. Upon that, the consuming of antidiabetic drugs has its regional peculiarities which condition the need in conduction of studies of pharmaceutical support on a level of the certain region.